Gravimetric analysis of stability of polymeric materials during exposure to chemical disinfectants at different temperatures. (September 2022) - Lee, Kang Hoon; Khan, Imtiaz Afzal; Lee, Yong - Soo; Kim, Jong Oh
Abstract: The goal of this study was to evaluate the impact of thermal and chemical aging processes on high-density polyethylene (HDPE), low-density polyethylene (LDPE), unplasticized polyvinyl chloride (U-PVC), and high-impact polyvinyl chloride (Hi-PVC) pipes. The materials were exposed to 1–10 ppm chemical disinfectants [chlorine dioxide (ClO2 ) and hypochlorite (HOCl)] at 40–80 °C for 1200 h. The diffusion properties of the materials were systematically analyzed based on the change in their sorption characteristics and activation energies according to the Arrhenius model. Moreover, the structural changes were analyzed with scanning electron microscopy (SEM), Fourier transform infrared (FTIR) radiation, and thermogravimetric analysis (TGA). The results show that the materials have Fickian characteristics in the aging environment. Specifically, the water sorption rates of HDPE and LDPE increase first and then decrease after reaching saturation (Ms); those of U-PVC and Hi-PVC its increasing continuously with different rate. This behavior of materials was prominent for ClO2 at high temperature and disinfectant dose because of polymeric chains crosslinking and rearrangement, extraction of monomers, and stable compounds removal during aging under exposed conditions. The deleterious effects decreased the activation energies of the materials and increased the concentrations of carbonyl groups [CO] via the formation of ketones, aldehydes, and carboxylic acids. The decomposition temperature increased with the changes in the material morphology and elemental contents under the investigated conditions. Moreover, LDPE and Hi-PVC were more severely affected in the thermal aging process with 10 mg.L −1 ClO2 at 80 °C. Graphical abstract: Image 1 Highlights: Materials show Fickian behavior under investigated conditions. Increase in Ms and decrease in Ea with decreasing equilibrium time during aging. ClO2 and 80 °C have stronger effects on LDPE and Hi–PVC. Increase in decomposition temperature due to increase in crosslink density.